Retrospective study shows that doxapram therapy avoided the need for endotracheal intubation in most premature neonates. (1st March 2017) - Flint, Robert; Halbmeijer, Nienke; Meesters, Naomi; van Rosmalen, Joost; Reiss, Irwin; van Dijk, Monique; Simons, Sinno
Abstract: Aim: Using doxapram to treat neonates with apnoea of prematurity might avoid the need for endotracheal intubation and invasive ventilation. We studied whether doxapram prevented the need for intubation and identified the predictors of the success. Methods: This was a retrospective study of preterm infants born from January 2006 to August 2014 who received oral or intravenous doxapram. Success was defined as no need for endotracheal intubation, due to apnoea, during doxapram therapy. Univariable and multivariable logistic regression analyses identified predictors of success during the first 48 hours of doxapram therapy. Results: Data on 203 patients with a median gestational age of 26.1 (interquartile range 25.1–27.4) weeks were analysed. During the first 48 hours of doxapram therapy, 157 (77%) patients did not need endotracheal intubation and 127 (63%) patients were successfully treated over the entire treatment course. The median postnatal age at the start of doxapram therapy was 20 days (interquartile range 12–30). Postnatal age and a lower fraction of inspired oxygen at the start of doxapram therapy were significant predictors of success (odds ratio 0.964, 95% confidence interval 0.938–0.991, p = 0.001). Conclusion: Oral and intravenous doxapram effectively treated most cases of apnoea in preterm infants, avoiding the need for intubation.